2015
DOI: 10.1002/bab.1411
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a novel PE_PGRS60 protein (Rv3652) of Mycobacterium tuberculosis H37Rv exhibit fibronectin‐binding property

Abstract: The binding of pathogenic bacteria to extracellular matrix components enhances adhesion and invasion of host cells. The host receptor proteins such as fibronectin (Fn) targeted to pathogenic ligands that have clinical importance. In the present study, we cloned, expressed, purified, and identified a novel Fn-binding protein from PE_PGRS60 (Rv3652) of Mycobacterium tuberculosis H37 Rv. The protein product of Rv3652 showed optimum binding efficiency to 10 ng Fn at 0.2 µg purified protein of PE_PGRS60 and 20 ng F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…Recent reports revealed that PE11 knockdown strains could significantly enhance fibronectin attachment protein production, contributing to the attachment to the host extracellular matrix ( Rastogi et al, 2017 ). PE_PGRS60 can bind to fibronectin, which results in enhanced adhesion and invasion ( Meena and Meena, 2016 ).…”
Section: Role Of Pe/ppe Proteins In Host–pathogen Interactionsmentioning
confidence: 99%
“…Recent reports revealed that PE11 knockdown strains could significantly enhance fibronectin attachment protein production, contributing to the attachment to the host extracellular matrix ( Rastogi et al, 2017 ). PE_PGRS60 can bind to fibronectin, which results in enhanced adhesion and invasion ( Meena and Meena, 2016 ).…”
Section: Role Of Pe/ppe Proteins In Host–pathogen Interactionsmentioning
confidence: 99%
“…The additional roles of PE/PPE protein are summarized. PE_PGRS60 (Rv3652) was a novel fibronectin-binding protein (Meena and Meena, 2016). PE_PGRS11, a potent phosphoglycerate mutase, mediates the immune invasion of bacteria to hypoxic conditions (Meena, 2015).…”
Section: Additional Roles Of Pe/ppe Proteinmentioning
confidence: 99%
“…FnBP complex constitutes antigen-85A, -85B, -85C (Ag85a, Ag85B, Ag85C) and FnBP A, B, C which play a crucial role in M. tuberculosis pathogenesis and also illustrate cell wall mycolyl transferase activity23. FnBPs mainly belong to proline glutamic polymorphic CG repetitive sequence family of genes present in mycobacteria242526. Previous studies have validated its binding to fibronectin (Fn), a multidomain glycoprotein on host surface22.…”
Section: Synergetic Effect Of Adhesion and Host Cell Signalling In Tbmentioning
confidence: 99%